O ser e a cultura na obra do naturalista Alexandre Rodrigues Ferreira: uma análise a partir da viagem filosófica no século XVIII - Ribeiro, Luciano Sá (2021)
The world of man and the cultural context located in the Amazon and its relationship with the European world in the century of enlightenment, will be given through norms, Eurocentric views, narrative constructions about the human and natural world. These data are present in the narratives of Alexandre Rodrigues Ferreira's philosophical journey. The aim is to analyze being and culture in the work of Alexandre Rodrigues Ferreira. How being and culture appear in the work of the naturalist during his journey through the Amazon. To approach the problem we use a qualitative research. From the bibliographical technical procedure; reading the material in an exploratory, selective, analytical, interpretative way and the methods; hermeneutic when we analyze the narratives and their interests, their intentionality and dialectic in the analysis of socio-historical discourses, the voices and dialogues present in this context. The reflection developed showed us that even if there were policies that avoided slavery, there were unofficial proposals that went against the freedom of the indigenous. If we look at these elements we will see that many visions about the indigenous peoples and the Amazon were aimed at inferiorization, with the purpose of conquering them and making them vassals of the king of Portugal. The relationship instituted between the European and the Amazonian man, during this process, left marks and proved changes in the life and cultures existing in this space. We conclude that these issues are not easy and require great commitment, for it is necessary to deconstruct established ideas and ideologies. Looking at the reality where we carried out our analysis, we find a web of relationships that intertwine through distinct relations, being and culture are inserted in the unveiling project; natural, geographic, human, and scientific